119th harmonic mode-locking in the fiber laser based on a novel saturable absorber thin film obtained by the sol-gel method. (January 2022) - Wang, Yongjie; Song, Chunyu; Zhang, He; Jin, Liang; Xu, Yingtian; Ma, Xiaohui; Zou, Yonggang
Highlights: A novel SA of TI/SiO2 based on sol-gel method can be prepared directly on the fiber end facet and have astable mode-locked operation. This TI/SiO2 SA is better than the SA based on organic film in the aging-resistant and the laser damage resistance. A harmonic mode-locking is realized successfully with this TI/SiO2 SA and the highest repetition rate is to 2.84 GHz. Abstract: A new kind of saturable absorber (SA) based on sol-gel technology was designed in this study. The integration of this SA is different from the traditional transmission coupling, which drops the TI/ SiO 2 sol-gel glass on the fiber end facet and forms a complete glass to cover the fiber core after drying naturally. According to the nonlinear optical character test, the modulation depth, saturable intensity and nonsaturable loss of this SA are 39.31%, 32.21 MW/ cm 2 and 13.41%, respectively. Besides, the SA based on sol-gel glass has a remarkable improvement in long-term stable mode-locking operation comparing with the SA based on organic film by aging-resistant testing and damage threshold of SA based on sol-gel glass increases by almost an order of magnitude. The fundamental mode-locking (FML) is observed at 1569 nm with pulse duration of 718 fs at the pump power of 90mW when this SA is integrated into the erbium-doped fiber (EDF) laser. As further increasing the pump power, the harmonic mode-locking (HML) appears. The highest harmonic order is to 119 with pulse duration of 4.48 ps at the pump power of 395mW. These results indicate that this TI/ SiO 2 SA prepared by the sol-gel method offers a new opportunity for the integration way of SA.